Information systems security and privacy 5th International Conference, ICISSP 2019, Prague, Czech Republic, February 23-25, 2019, Revised Selected Papers /: 5th International Conference, ICISSP 2019, Prague, Czech Republic, February 23-25, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available